PERAN PEMBELAJARAN BERBASIS ALAM TERBUKA DALAM MENINGKATKAN OBSERVASI DAN KREATIVITAS SISWA SD - Elya Sulistia Safitri; Haifaturrahmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of outdoor-based learning in enhancing observation skills and creativity among elementary school students. The research employs a Systematic Literature Review (SLR) method by reviewing scientific publications indexed in Scispace, Elicit, Google Scholar, and DOAJ from 2015 to 2025. The findings indicate that outdoor-based learning effectively improves students’ observation, creativity, and critical thinking skills through contextual and meaningful direct learning experiences. In addition to strengthening cognitive aspects, this approach also fosters motivation, collaboration, and environmental responsibility.